2021
DOI: 10.3390/biology10020168
|View full text |Cite
|
Sign up to set email alerts
|

The Overall Efficacy and Outcomes of Metronomic Tegafur-Uracil Chemotherapy on Locally Advanced Head and Neck Squamous Cell Carcinoma: A Real-World Cohort Experience

Abstract: Metronomic chemotherapy inhibits tumor growth by continuous administration of lower-dose chemotherapy. Our study aimed to demonstrate the outcomes of metronomic chemotherapy with tegafur–uracil in locally advanced head and neck squamous cell carcinoma (LA HNSCC). This was a retrospective study including 240 patients with LA HNSCC. After standard treatment, 96 patients were further treated with metronomic tegafur-uracil, and 144 patients were not. No statistical differences were found between both groups with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Metronomic chemotherapy (MC) utilizes lower doses of chemotherapeutic drugs than the MTD of conventional chemotherapy. It is administered at regular intervals without any long recovery phases between cycles, thereby maintaining a consistent drug level in the blood [6,[8][9][10].…”
Section: Modes Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metronomic chemotherapy (MC) utilizes lower doses of chemotherapeutic drugs than the MTD of conventional chemotherapy. It is administered at regular intervals without any long recovery phases between cycles, thereby maintaining a consistent drug level in the blood [6,[8][9][10].…”
Section: Modes Of Actionmentioning
confidence: 99%
“…Low-dose, repetitive, regular medication delivery without extended drug-free intervals is the hallmark of metronomic therapy [ 5 ]. Yeh et al have reported the antitumor effects of tegafur-uracil as a metronomic agent in advanced oral cancer and nasopharyngeal carcinoma [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary, initial treatment guidelines for HNSCC vary, according to the location of the tumour and stage of the disease, and can be improved with metronomic chemotherapy [ 61 ]. The mechanism of action for all “classic” chemotherapeutics is typically based on cytotoxicity, targeting generic, non-cancer specific processes such as mitosis and DNA damage/damage response.…”
Section: Targeting Oncogenic Pathways In Hnsccmentioning
confidence: 99%
“… 4 , 7 , 8 Multiple retrospective and prospective studies have suggested that adjuvant metronomic chemotherapy may improve outcomes in HNSCC. 9 , 10 , 11 , 12 , 13 In view of the encouraging data from palliative setting and small clinical data in the adjuvant setting we decided to test it in the adjuvant setting. Hence we did a phase 3 randomized study to assess whether adjuvant treatment with the metronomic combination of methotrexate and celecoxib leads to improvement in outcome in locally advanced head and neck cancers post radical chemoradiation.…”
Section: Introductionmentioning
confidence: 99%